BETWEEN LOVE AND GUILT: Psychoanalytic analysis of the bond between mother and son in the film 'We Need to Talk About Kevin' - Andrade, Arthur Henrique de (2023)
This article aims to analyze the feeling of guilt in the relationship between mother and child using the character Kevin, from the film “We Need to Talk About Kevin”, as an illustrative example of this dynamic. To achieve this, a qualitative methodology of an exploratory nature is adopted, based on a documentary analysis that considers Melanie Klein's psychoanalytic theory and the use of film as a way of analyzing the phenomenon. The study contributes to understanding the importance of communication between parents in raising a child. The results indicated the presence of guilt on the part of the mother towards the child, which makes reparation between them impossible. The lack of desire and denial of motherhood directly impacts the way they relate to each other, evidenced by Kevin's sadistic resistance to the maternal object.